Masa Jabatan Kepala Desa Bangunharjo Kecamatan Sewon Kabupaten Bantul: Ditinjau dari Undang-Undang Nomor 6 Tahun 2014 tentang Desa - Iis Qomariyah (UIN Sunan Kalijaga Yogyakarta, 2014)
The research concludes that the legal basis used Bangunharjo village chief areLaw No. 22 of 1999 on Regional Government. In Article 96 describes the